Nutraceuticals and innovative food products for healthy living and preventive care - Verma, Amit, 1983-; Srivastava, Kajal, 1978-; Singh, Shivom, 1978-; Singh, Hukum, 1983- (IGI Global, 2018)
"This book's research brings a revolution in the field of dietary products and numbers of industries are growing rapidly using these natural products. The book gives us a better understanding of what is an optimal diet, but has allowed food and nutraceutical companies to market products with specific health claims and fortify existing foods"- Resumé vydavatel
Keywords: nutraceutika; potravní doplňky; potravinářská technologie; nutraceuticals; dietary supplements; food technology; elektronické knihy; kolektivní monografie; electronic books; collective monographs